Sociocognitive factors associated with lifestyle intervention attrition after successful weight loss among participants with prediabetes—The PREVIEW study. Issue 3 (11th March 2020) - Huttunen‐Lenz, Maija; Raben, Anne; Meinert‐Larsen, Thomas; Drummen, Mathijs; Macdonald, Ian; Martínez, José Alfredo; Handjieva‐Darlenska, Teodora; Poppitt, Sally D.; Jalo, Elli; Muirhead, Roslyn; Schlicht, Wolfgang
Abstract: Introduction: Major risk factors for type 2 diabetes are lifestyle choices such as lack of physical activity (PA) and poor diet. Many individuals either do not take part or struggle to complete interventions supporting lifestyle changes. Demographic and theory‐based sociocognitive factors associated with PREVIEW intervention attrition after successful weight loss were examined. Methods: Participants (1, 856) who started the weight maintenance phase after completion of low‐energy diet were retrospectively divided into three clusters depending on the point they left the trial. Discriminant analysis examined which demographic and theory‐based sociocognitive variables were associated with cluster membership. Results: Most of the participants were women and well‐educated. Two discriminant functions were calculated ( χ 2 (24) = 247.0, p  ≥ .05, d  = 0.78). The demographic variables, such as age and ethnicity, and the social cognitive variable outcome expectancies on the other side were associated with cluster membership. Older age, Caucasian ethnicity, and fewer expected disadvantages of PA were associated with high success. Discussion: The discriminant model gave insight into some factors associated with early attrition. For practitioners planning interventions it underlines the necessity to take extra attention to younger participants and to those being afraid that being physically active causes unpleasant ramifications.